Kajian Potensi Pembangkit Listrik Tenaga Biomassa Sawit - Sri Wahyuni; Aldri Frinaldi; Dasman Lanin; Rembrandt Rembrandt (Jurnal Sains dan Ilmu Terapan, 2024)
The palm oil industry, in addition to producing the main product of CPO, also generates large amounts of solid waste (biomass). Palm biomass is a type of renewable energy that can be utilized as fuel for biomass power plants (PLTBS - Pembangkit Listrik Tenaga Biomassa Sawit). Empty fruit bunches (TKKS) have significant energy potential as fuel for electricity generators. The energy potential of TKKS can be seen from its calorific value, which is 18,795 kJ/kg. The heating value of dry TKKS is 18.8 MJ/kg, with an energy conversion efficiency of 25%, which is equivalent to 2.3 Mwe. Financial calculations for all criteria show a Net Present Value (NPV) of IDR 65,582,439, an Internal Rate of Return (IRR) of 15%, and a Payback Period (PBP) of 4.98 years, indicating that the effort to convert palm biomass into electricity is still financially viable.